Analisis Tingkat Pengetahuan Kesehatan Gigi dan Mulut Ditinjau dari Jenis Kelamin dan Kelas pada Anak Sekolah Dasar di Mi Sudirman Kawengen 01 - Unafa Fitria Rista Putri; Herry Susanto; Indra Tri Astuti (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aimed to analyze the level of oral and dental health knowledge among elementary school children in relation to gender and grade level. A quantitative descriptive cross-sectional design was employed as a field-based study conducted at MI Sudirman Kawengen 01 in August 2025. The study population comprised all students in grades III to VI, with total sampling applied to obtain 106 respondents. Data were collected using a structured questionnaire consisting of 19 validated and reliable items measuring oral and dental health knowledge. Univariate analysis was used to describe the distribution of knowledge levels, while bivariate analysis employed the Mann–Whitney test to assess gender-based differences and the Kruskal–Wallis test followed by post hoc analysis to examine differences across grade levels. The results indicated that most respondents demonstrated a moderate level of knowledge. Statistically significant differences were found between male and female students, with females showing higher knowledge levels. Significant variations were also observed across grade levels, particularly between lower and higher grades. These findings highlight the influence of developmental and demographic factors on children’s oral health knowledge and underscore the importance of targeted, stage-appropriate oral health education in primary schools.